A facile way to synthesize an intrinsically ultraviolet-C resistant tough semiconducting polymeric glass for organic optoelectronic device application. (30th October 2020) - Shankar, Uday; Gupta, Chaitanya R.; Oberoi, Deepa; Singh, Bhanu P.; Kumar, Ashok; Bandyopadhyay, Anasuya
Abstract: In this investigation, we have developed a new semiconductive Polymeric Transparent Matrix (PTM) as a substitute to the glass substrate used in a conventional optoelectronic device. Initially, we have synthesized Poly(methyl methacrylate) (PMMA) and series of its copolymers with Styrene in different weight percent (wt.%) ratio via solution polymerization process. The obtained polymers were characterized using various techniques to understand the effect of introducing different proportions of Styrene comonomers on PMMA backbone. The optimum composition of PTM was chosen based on copolymer's mechanical properties, optical transparency, and ultraviolet (UV) shielding properties. Then, a series of nanocomposites consisting of optimized PTM and various wt.% of Multiwalled Carbon Nanotubes (MWCNT) as a conductive filler were fabricated to increase the conductivity of PTM. A steep increase (̴10 9 fold) in bulk electrical conductivity was observed in case of 0.25 wt% MWCNT loaded optimized composite matrix, along with the retention of a good amount of optical transparency (88% at 550 nm) and 100% UV-C shielding. This optimized nanocomposite has also shown amelioration in mechanical properties as a result of uniform dispersion of MWCNT. These remarkable attributes favor the use of this optimized semiconducting PTM as a potential transparent substrate for next-generation organic optoelectronic devices. Graphical abstract: Image 1 Highlights: A tough, transparent, semi-conductive, light-weight polymer glass matrix has been developed for optoelectronic applications. A series of copolymers of MMA & Sty were synthesized to study the effect of the introduction of Sty on different properties. Based on mechanical and optical properties, P(MMA70 - co -Sty30 ) found to be the best substrate for the optoelectronic device. Different proportions of MWCNT were added to the optimised polymer substrate as conducting filler to reduce bulk resistivity. The optimized semiconducting matrix shows better optical property in some regions compared to the conventional glass matrix.